Tactile sensitivity, tactile acuity, and affective touch: from childhood to early adolescence. (2nd January 2019) - Zingaretti, Pietro; Petta, Anna Maria; Cruciani, Gianluca; Spitoni, Grazia Fernanda
Abstract: The development of somatosensation and affective touch acquires a central role throughout our lives, for several reasons. In adults, these functions are driven by different, neuroanatomically and functionally segregated fibres. To date, very little is known about the basic features of these fibres in childhood and this lack of knowledge is mirrored in the affective touch domain, where there are no studies on the main physiological features of the tactile processes linked to the stimulation of the hairy skin, namely the preferential site of affective touch. Thus, our study aims to analyze (1) tactile sensitivity and tactile acuity of children's hairy forearms; (2) a possible dissociation between somatosensation and the affective touch; and (3) the presence/absence of the perception of affective touch already in childhood. To these aims, participants (160 children, aged 6 to 14 years), were administered with the Von Frey (tactile sensitivity) and the 2 Point Discrimination (tactile acuity) tests. Affective touch was measured following the classic protocol and pleasantness ratings were recorded. Our findings showed a correlation between age and somatosensation, suggesting a progressive reduction of sensitivity and acuity as age grows. Further, there was no overlap between affective touch and somatosensation, suggesting a behavioural segregation. Lastly, we found higher pleasantness ratings for Affective versus Neutral stimulations at all ages and an enhanced preference for Affective as age grows. We concluded that both somatosensation and affective touch are already present as two separate components of touch in childhood and change as a function of age.